Holy or blessed water? Legal and liturgical analysis - SAJ, MAREK (Prawo Kanoniczne, 2017)
During celebration of a different kind of liturgical acts water is used frequently. According to liturgical acts water should be previously blessed with the appriopriate prayer. After that act of prayer water becomes blessed water. However, within the Church the notion „holy water” is widely applied. Legal and liturgical research shows that the only proper phrase is „aqua benedicta” - blessed water. It is difficult to explain why that improper notion „holy water” is so strongly rooted in Polish reality. Probably it derives from the fact that the phrase „holy water” is introduced in liturgical books. It seems necessary to provide formation for both laity and clergymen to make them aware of the fact why the notion „blessed water” is the only proper one.